Gestão democrática na perspectiva do diretor de escola - Silveira, Jose dos Santos [UNIFESP] (2016)
This research investigated the perspective of the public school principal on democratic management in São Paulo city. This study was prompted by the question that aims to learn what the principals of municipal schools think about the democratic management and how they perform it in everyday school life. Thus, the main objective was to identify and analyze the perspective of the school principals on the democratic management of public schools, with reference to the constitutional principle (Federal Constitution of 1988). Regarding specific objectives, from the school principals? perspective, their views on the subject of democratic management were analyzed, which instances and democratic management mechanisms are used within the school, and the principals? concepts about participation and collective decisions. Starting from the understanding that education is a public policy, the relationships between education, State and democracy were studied to build an understanding of the democratic management in public education. Therefore, it was based on authors such as Carlos Nelson Coutinho, Maria Victória M. Benevides, Vitor Paro, Nicos Poulantzas e Antônio Gramsci. To analyze the issue of democratic management in public schools, bibliographic and documentary research was carried out in addition to a questionnaire to elementary school principals in São Paulo city. The data enabled the observation of a tendency on the part of the school principal to restrict the concept of democratic management to the formal level, valuing the rules and regulations issued by the municipal administration central organs, while internally in the school, disregarding the active and direct participation in the decision-making process of members from the school community, especially parents or guardians and, clearly, students. The data indicated that the principal expects from the central organs the guidelines on how the organization and participation in school management should be and, in general, they consider the directives from above in a formal manner, according to the legal and juridical aspects. It was also verified that there is little investment in order to promote greater social involvement, open discussions, debates and the possibility of greater participation of the school and local community.